UPAYA PEMERINTAH INDONESIA DALAM MENGATASI MASALAH HUMAN TRAFFICKING PADA TAHUN 2006-2018 TERHADAP PEKERJA MIGRAN INDONESIA DI MALAYSIA - Ani Khoirunnisa; Mayasari Basri (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2020)
This research takes the theme of the efforts made by the Government of Indonesia in overcoming the problem of Human Trafficking in 2006-2018 against Indonesian Migrant Workers in Malaysia through multi track diplomacy. These efforts were carried out both on the basis of initiatives from the Government of Indonesia itself and the wishes of both parties manifested in the form of bilateral cooperation. However, in the process of its realization, several obstacles were encountered that impeded the efforts made, the obstacles encountered were both from within Indonesia and also inseparable from its collaborative partner, namely Malaysia. In this paper the writer question about how the efforts made by the Government of Indonesia in overcoming the problem of Human Trafficking in 2006-2018 against Migrant Workers who are in Malaysia. In answering the research questions the writer used the theory of Human Security, Human Trafficking, Bilateral Cooperation and also Multi Track Diplomacy. In the process of proving and also analyzing the writer used qualitative research methods and explanatory data presentation. For the hypothesis proposed by the writer is that the Government has made several efforts through Multi Track Diplomacy using track one namely G to G in this case carried out by the Government of Indonesia with the Government of Malaysia, then by using the method of Track Two, in this case carried out by BNP2TKI, then Track Five by conducting socialization and education in schools. However, the independent efforts undertaken by Indonesia and also bilateral cooperation carried out with Malaysia have not yet gotten maximum results, this is because of the obstacles faced. In general, constraints originating from within the country come from the weakness of the law enforcement process that applies in Indonesia concerning human trafficking. Then the obstacles that come from Malaysia are generally because it is difficult to reach an agreement in an effort to protect Migrant Workers who come from Indonesia, this is because of differences in the interests of the two countries in looking at the Migrant Workers issue